The dancer upstairs [videorecording (DVD)] - Malkovich, John; Shakespeare, Nicholas, 1957-; Bardem, Javier, 1969-; Botto, Juan Diego; Morante, Laura, 1956- (20th Century Fox Home Entertainment, 2003)
As a Latin American nation nears collapse, idealistic policeman Agustin Rejas faces his greatest challenge: to catch the mysterious terrorist leader Ezequiel. Mass panic sets in as the terrorist attacks become more ferocious, and Rejas finds himself drawn to Yolanda, his daughter's beautiful ballet teacher. As the search for Ezequil comes nearer, he and Yolanda must choose between love, country or self.